Добро пожаловать в ад: [роман] / А. М. Дышев - Дышев Андрей Михайлович (Черная кошка, 2003)
Экземпляры: оиф (20140521) / Инвентарный номер: 34807 / Цена: 59.00 / Авт.знак: Д 91 / ГРНТИ: 17.82 / ББК: 84(2Рос-Рус)6-4